Halal Tourism Destination Development Model - RUSLI, Meizar; FIRMANSYAH, Riza; MBULU, Yustisia Pasfatima (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.9.6(30).19, 2019)
The development of halal tourism needs an advancement, considering its vast market potential in Indonesia in the midst of readiness issues. The purpose of this study was to analyze the psychological orientation: perceptions, motivations, and preferences of stakeholders in developing halal tourism destinations. In addition, to formulate a development model for halal tourism destinations in Indonesia. The population in this study comprised of tourists; tourism business owners; as well as the officials taking charge in halal tourist destinations, and halal tourism products and brands. Data collection of existing conditions was conducted in regard to halal tourism product offerings. Afterward, the assessment of various potential halal tourism resources in Indonesia was carried out through a scoring system. The results of this study showed that the gradual development of halal tourism destinations has main priority in the development of halal food & beverages at the level of 0.49; the availability of places of worship at the level of 0.34; the availability of recreational facilities for different gender at the level of 0.090; and the atmosphere of Islam at the level of 0.068. The right tourism development model begins with the classification of tourism with an Islamic approach, namely: Level 1 - Conventional Tourism, Level 2 - Muslim Friendly Tourism, Level 3 - Muslim Religious Tourism and Level 4 - Halal Tourism. The optimization model developed in this study is expected to be beneficial for governments, practitioners, and academicians in designing halal tourism development policies, as well as other institutions that have particular interest to halal tourism expansion in Indonesia.